1997
DOI: 10.1111/j.1540-8167.1997.tb00840.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐Rate Atrial Pacing as an Innovative Bridging Therapy in a Neonate with Congenital Long QT Syndrome

Abstract: High-rate atrial pacing with 2:1 AV block is presented as a novel and "bridging" therapy for neonatal long QT syndrome and 2:1 AV block with ventricular arrhythmias. Definitive therapy with ICD implantation was then possible when patient size was substantially increased. The electrophysiologic response to intentional elevation of the serum potassium suggests a genetic defect in an inward potassium channel and demonstrates a possible therapy of long QT syndrome in some future patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…23 LQTS with AV conduction disturbances has been reported often in infants or young children with a major QTc prolongation, but without any positive familial history, [23][24][25][26][27][28] as in our case. Indeed, the fast atrial rate, which characterizes pediatric sinus rhythm, can lead to functional AV block in the setting of dramatic prolongation of ventricular repolarization as the P wave falls within the T wave.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…23 LQTS with AV conduction disturbances has been reported often in infants or young children with a major QTc prolongation, but without any positive familial history, [23][24][25][26][27][28] as in our case. Indeed, the fast atrial rate, which characterizes pediatric sinus rhythm, can lead to functional AV block in the setting of dramatic prolongation of ventricular repolarization as the P wave falls within the T wave.…”
Section: Discussionmentioning
confidence: 81%
“…This form mainly affects neonates and seems to be associated with a worse prognosis. 24,28,29 Electrophysiological studies have confirmed the location of such blocks at the ventricular level associated with major prolongation of the refractoriness in the ventricular muscle. 25,29 In contrast, our results provide evidence for an infra-Hisian block location in the His-Purkinje system rather than at the ventricular level.…”
Section: Discussionmentioning
confidence: 89%
“…(A) Non-pause dependent torsade de pointes in a neonate 47. There is sinus tachycardia with marked T wave alternans.…”
Section: Resultsmentioning
confidence: 99%
“…In addition hypokalaemia lowers the threshold for arrhythmias in the long QT syndrome and rapidly increasing the serum potassium improves repolarisation; in fetuses suspected of having the long QT syndrome maternal serum potassium should be more than 4 nmol/L. Potassium supplements may have to be given, and sometimes spironolactone 17 . In our case the maternal serum potassium was normal (4.1 nmol/L) at the end of the first trimester in spite of hyperemesis gravidarum.…”
Section: Discussionmentioning
confidence: 58%